PENGARUH BEBAN KERJA DAN KUALITAS KERJA TERHADAP KINERJA KARYAWAN AKADEMI FARMASI INDONESIA YOGYAKARTA DI MASA PANDEMI - Imam Pratama; Yunita Fitri Wahyuningtyas (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2021)
This study aims to: 1) To analyze the effect of the pandemic on the workload and quality of work of employees who work at home (WFH), 2) To analyze the effect of the pandemic on employee performance at the Indonesian Pharmacy Academy Campus in Yogyakarta, 3) To analyze workload and work quality on employee performance at the Indonesian Pharmacy Academy in Yogyakarta. This study aims to determine the effect of workload and work quality on employee performance at the Indonesian Pharmacy Academy in Yogyakarta during the pandemic period. The type of research used in this research is quantitative. The focus of this research is to find out how workload and work quality affect employee performance at the Yogyakarta Indonesian Pharmacy Academy during the pandemic. This research was conducted to improve the performance of employees at work so that they can carry out their work and activities well despite implementing a work from home (WFH) system. With the control of employee performance, controlling the workload in accordance with the ability of employees and the quality of work that will make the Indonesian Pharmacy Academy Yogyakarta campus maintain quality services.